Plan de exportación de alcohol orgánico para el consorcio agro-artesanal dulce orgánico “CADO”, al mercado de Paris – Francia, año 2011 - Piza Vivas, Calixto Eliodoro (2012)
The business of the alcohol that is produced by families in the foothills of the parish of San Luis Pambil is traditionally little paid prices which only reach to sell by week of 40 to 70 dollars in the local market. Added to this is the lack of knowledge of the families in order to enter and marketed in new markets, where this product receives due recognition for their organic quality and greater economic value. International markets constitute the great opportunity to negotiate an organic quality product because their industries demand excellent quality raw to produce the finest perfumes and spirits consumed in the world. The export of organic alcohol to international markets shows the possibility of improving the quality of life of many families, thus as the generation of sources of work because there are many people involved in this process, which is why research on the exp. With the results of the market research made to producers of alcohol could be check and accept the hypothesis that says the producers of organic alcohol of the Bolívar province if you are interested in marketing your product to international markets through market to the French market. The raw material used by all producers is purely organic free of chemical pollutants. In this way producers manage their sugarcane crops i.e. organic traditional manner, instead of farmers who seek only intensive agriculture to obtain better returns are those of sugar cane. Organic alcohol producers must sign agreements to ensure their participation in export to Europe, in this way they handle volumes for exports and also ensure a fair price for your product. CADO receives from farmers who grow sugar cane organic alcohol your excellent product. Organic alcohol producers must sign agreements to ensure their participation in export to Europe, in this way they handle volumes for exports and also ensure a fair price for your product. CADO receives from farmers who grow sugar cane organic alcohol product of their excellent land without making application of agro-chemicals harmful to human health; alcohol must be 70 ° GL for medical as antiseptic and 96.3 ° GL for drinking alcohol valid use to develop the finest perfumes and liquors.